Cautious Application of Pleural N-Terminal Pro-B-Type Natriuretic Peptide in Diagnosis of Congestive Heart Failure Pleural Effusions among Critically Ill Patients - Yeh, Jiann-Horng (PLoS One, 2014)
BACKGROUND AND OBJECTIVE: Several studies on diagnostic accuracy of pleural N-terminal pro-B-type natriuretic peptide (NT-pro-BNP) for effusions from congestive heart failure (CHF) conclude that pleural NT-pro-BNP is a useful biomarker with high diagnostic accuracy for distinguishing CHF effusions. However, its applicability in critical care settings remains uncertain and requires further investigations. METHODS: NT-proBNP was measured in pleural fluid samples of a prospective cohort of intensive care unit patients with pleural effusions. Receiver operating characteristic curve analysis was performed to determine diagnostic accuracy of pleural NT-proBNP for prediction of CHF effusions. RESULTS: One hundred forty-seven critically ill patients were evaluated, 38 (26%) with CHF effusions and 109 (74%) with non-CHF effusions of various causes. Pleural NT-proBNP levels were significantly elevated in patients with CHF effusions. Pleural NT-pro-BNP demonstrated the area under the curve of 0.87 for diagnosing effusions due to CHF. With a cutoff of 2200 pg/mL, pleural NT-proBNP displayed high sensitivity (89%) but moderate specificity (73%). Notably, 29 (27%) of 109 patients with non-CHF effusions had pleural NT-proBNP levels >2200 pg/mL and these patients were more likely to experience septic shock (18/29 vs. 10/80, P<0.001) or acute kidney injury (19/29 vs. 9/80, P<0.001). CONCLUSIONS: Among critically ill patients, pleural NT-proBNP measurements remain a useful diagnostic aid in evaluation of pleural effusions. However, patients with non-CHF effusions may exhibit high pleural NT-proBNP concentrations if they suffer from septic shock or acute kidney injury. Accordingly, it is suggested that clinical context should be taken into account when interpreting pleural NT-proBNP values in critical care settings.